Non-destructive measurement of nitrogen status of leafy ornamental cuttings by near infrared reflectance spectroscopy (NIRS) for assessment of rooting capacity. (August 2016) - Lohr, Dieter; Tillmann, Peter; Zerche, Siegfried; Druege, Uwe; Rath, Thomas; Meinken, Elke
Abstract : An adequate nitrogen supply to stock plants is a well-known key factor in adventitious root formation of herbaceous ornamental cuttings. Both slight deficiency and luxury amount of nitrogen in the tissue can impair rooting. Due to a lack of fast, cheap and reliable analytical methods, parameters characterising the nitrogen status of cuttings are not used as quality indicators. Near infrared reflectance spectroscopy (NIRS) might bridge this gap, especially if sample preparation such as drying or grinding is avoided. NIR spectra of intact chrysanthemum and pelargonium cuttings were taken and partial least square regression models were developed for various nitrogen fractions as well as for total nitrogen. Calibration equations with high prediction performance were developed for insoluble, organic and total nitrogen (R 2 > 0.8). Calibration models for various soluble nitrogen fractions were at least suitable for a rough screening (R 2 > 0.6). In a second experiment, calibration models were extended to poinsettia, impatiens and osteospermum cuttings by adding a few samples to the calibration data set. Thus, analysing nitrogen status of ornamental cuttings by NIRS might be a valuable tool for optimisation of stock plant cultivation and assessment of rooting capacity of cuttings. Highlights: Nitrogen status of ornamental cuttings can be predicted by NIRS. No sample preparation as drying or chopping is necessary. Calibration models can be extended to new species with only few samples.